Cell Membrane‐Coated Magnetic Nanocubes with a Homotypic Targeting Ability Increase Intracellular Temperature due to ROS Scavenging and Act as a Versatile Theranostic System for Glioblastoma Multiforme. Issue 18 (7th August 2019) - Tapeinos, Christos; Tomatis, Francesca; Battaglini, Matteo; Larrañaga, Aitor; Marino, Attilio; Telleria, Iker Aguirrezabal; Angelakeris, Makis; Debellis, Doriana; Drago, Filippo; Brero, Francesca; Arosio, Paolo; Lascialfari, Alessandro; et al.
Abstract: In this study, hybrid nanocubes composed of magnetite (Fe3 O4 ) and manganese dioxide (MnO2 ), coated with U‐251 MG cell‐derived membranes (CM‐NCubes) are synthesized. The CM‐NCubes demonstrate a concentration‐dependent oxygen generation (up to 15%), and, for the first time in the literature, an intracellular increase of temperature (6 °C) due to the exothermic scavenging reaction of hydrogen peroxide (H2 O2 ) is showed. Internalization studies demonstrate that the CM‐NCubes are internalized much faster and at a higher extent by the homotypic U‐251 MG cell line compared to other cerebral cell lines. The ability of the CM‐NCubes to cross an in vitro model of the blood‐brain barrier is also assessed. The CM‐NCubes show the ability to respond to a static magnet and to accumulate in cells even under flowing conditions. Moreover, it is demonstrated that 500 µg mL −1 of sorafenib‐loaded or unloaded CM‐NCubes are able to induce cell death by apoptosis in U‐251 MG spheroids that are used as a tumor model, after their exposure to an alternating magnetic field (AMF). Finally, it is shown that the combination of sorafenib and AMF induces a higher enzymatic activity of caspase 3 and caspase 9, probably due to an increment in reactive oxygen species by means of hyperthermia. Abstract : Cell membrane‐coated nanocubes (CM‐NCubes) present enhanced uptake from homologous cell lines and demonstrate increased apoptosis under the combinatory effect of an alternating magnetic field and of the drug sorafenib. Moreover, the scavenging ability of the CM‐NCubes leads to a controlled generation of oxygen, and to an intracellular temperature increase.